2019
DOI: 10.1155/2019/8676410
|View full text |Cite
|
Sign up to set email alerts
|

The Ovotransferrin-Derived Peptide IRW Attenuates Lipopolysaccharide-Induced Inflammatory Responses

Abstract: IRW (Ile-Arg-Trp), a bioactive peptide isolated from egg ovotransferrin, has been shown to exert anti-inflammatory effects. In this study, the effects of IRW on inflammatory cytokines and microbiota were explored in human umbilical vein endothelial cells (HUVECs) and a lipopolysaccharide (LPS)-induced rat model of inflammatory peritonitis. Rats were injected intraperitoneally with LPS to establish peritonitis. HUVECs were exposed to IRW for 12 h before introducing LPS. Notably, IRW exerted beneficial effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…A large number of experimental results indicate that colonic inflammation is accompanied by a decrease in colon length and other different degrees of morphological damage (Gearry et al, 2009; Gadaleta et al, 2011). Accordingly, IRW and IQW treatment appears to play a role in colonic inflammation (Jiao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of experimental results indicate that colonic inflammation is accompanied by a decrease in colon length and other different degrees of morphological damage (Gearry et al, 2009; Gadaleta et al, 2011). Accordingly, IRW and IQW treatment appears to play a role in colonic inflammation (Jiao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yu et al, (2019) exhibited potent ACE-inhibitory of ovotransferrin hydrolysates of 19 enzymes and one combination obtained from in silico hydrolysis. In addition, the peptides of ovotransferrin possess various immunomodulatory activities (Liu et al, 2017;Jiao et al, 2019), anti-inflammatory (Wang et al, 2017), and cytotoxic (Yi et al, 2017) activities.…”
Section: Introductionmentioning
confidence: 99%
“…In an in vivo study, the Ile-Arg-Trp from ovotransferrin inhibited lipopolysaccharide (LPS)-induced peritonitis in rat models by inhibiting the synthesis of serum TNF and IL-8 and myeloperoxidase. Also, Ile-Arg-Trp treatment increased the Shannon index and decreased the Simpson index and suggested that modification of gut microbial diversity due to the potential ability of Ile-Arg-Trp to enhance the barrier properties of the intestine (Jiao et al, 2019) (Table 2).…”
Section: Immunomodulatory and Anti-inflammatory Activitymentioning
confidence: 99%